Dukungan Sosial Keluarga Terhadap Subjective well-being Lansia: Systematic Literature Review - Shalma Fadilla; Nadira Ananda Putri; Rahmawati Agustia; Rahmadianti Aulia (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
The aging population continues to increase globally, raising serious concerns about their psychological well-being. This study aims to examine the role of family social support on subjective well-being (SWB) in older adults through a systematic literature review. Using the PRISMA protocol, four empirical articles published between 2021 and 2026 were selected from the Sciencedirect database. The results consistently show that emotional support from family, particularly from children, is the strongest predictor of life satisfaction in older adults across various cultural contexts. Instrumental support demonstrates a more complex pattern, where material or physical assistance can actually reduce older adults' sense of autonomy and selfesteem. Moderation factors such as culture, gender, region, and income level have been shown to influence the relationship between family support and subjective well-being (SWB). These findings underscore the importance of a contextualized and segmented approach in older adult support programs.